VALIDITY, PRACTICALITY AND EFFECTIVENESS OF A WEB-BASED INSTRUCTIONAL MATERIAL BASED ON LEARNING STYLES - Hesti Wahyuni Anggraini; Zuraida; Rita Hayati; Dwi Maharrani; Nova Lingga Pitaloka (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2024)
The shifting of teaching and learning mode results in the urgency of the development of instructional materials. Ironically, the availability of web-based instructional reading material on the basis of learning style is still limited. This developmental study examined data qualitatively and quantitatively from 16 questionnaire respondents, six interviewees and two lecturers to investigate the needs of developing instructional materials, the extent to how lecturers shaped their beliefs, students’ reading level, and students’ learning styles. This study also aimed at finding out the validity, practicality, and the effectiveness of developed product. Three students involved in one-to-one evaluation, nine students in small group evaluation and 17 students in the field test. This research implemented a four-stage model by Akker. Formerly, the result of analysis phase represented some analysis points. Furthermore, the product was highly valid on its content, construct and technology use with average score 4.4. The average scores of practicalities were 4.1 in one-to-one evaluation and 4.2 in small group evaluation. High validity with the score 4.3 was the result of the field test. Potential effect was also high in the average score of reading test, 86.47. This study, expectedly, gives favourable impact to the teachers and students in the future.